EKSPLORASI GEOARKEOLOGI SITUS PALEOLITIK DI PULAU SERAM, PROVINSI MALUKU [Geoarchaeological Exploration of Paleolitical Sites on The Island of Seram, Moluccas Province] - Intan, Muh Fadhlan S (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2017)
East Seram District, Central Maluku, and West Seram regency is located on the island of Seram, where research was conducted, save a lot of cultural, one of the paleolithic period, which is a long time not received attention from environmental researchers. It is used as the basis of the main issues that include geology in general. Therefore, the purpose of this study was to perform surface geological mapping in general as one of the efforts to provide geological information, while the goal is to determine aspects of geomorphology, stratigraphy, structural geology associated with the existence of paleolithic sites in the study area. The research method begins with a literature review, surveys, analysis, and interpretation of field data. Environmental scanning provides information about the landscape consists of plains morphological units, units of corrugated morphology weak, strong corrugated morphology unit, and units of karst morphology. The river berstadia old-mature river stadium, periodical/permanent river, and river episodic/intermittent river. Constituent rock is sandstone, limestone, marl, andesite, tuff, schist, volcanic breccias, reef limestones, conglomerates, and alluvial. Geological structures such as faults and folds. Ceram Research discovered 14 Paleolithic sites. From the analysis of petrology, lithic tools made of jasper rocks, chert, metalimestone, flint, and quartzite. Rock as raw material litik tool, found in the middle of Seram Island, then spread to the west and to the east which has a flat relief.   ABSTRAKKabupaten Seram Bagian Timur, Kabupaten Maluku Tengah, dan Kabupaten Seram Bagian Barat terletak di Pulau Seram, yang menjadi lokasi penelitian, menyimpan banyak tinggalan budaya, salah satunya dari masa paleolitik, yang sekian lama tak mendapat perhatian dari para peneliti lingkungan. Hal inilah yang dijadikan dasar permasalahan utama yang mencakup geologi secara umum. Oleh sebab itu, maksud penelitian ini dalah untuk melakukan pemetaan geologi permukaan secara umum sebagai salah satu upaya untuk menyajikan informasi geologi, sedangkan tujuannya adalah untuk mengetahui aspek-aspek geomorfologi, stratigrafi, struktur geologi yang dikaitkan dengan keberadaan di situs-situs paleolitik wilayah penelitian. Metode penelitian diawali dengan kajian pustaka, survei, analisis, dan interpretasi data lapangan. Pengamatan lingkungan memberikan informasi tentang bentang alamnya terdiri yang dari satuan morfologi dataran, satuan morfologi bergelombang lemah, satuan morfologi bergelombang kuat, dan satuan morfologi karst. Sungainya berstadia sungai dewasa-tua, sungai periodik/permanen, dan sungai episodik/ intermittent. Batuan penyusun adalah batupasir, batugamping, napal, andesit, tufa, sekis, breksi volkanik, batugamping terumbu, konglomerat, dan aluvial. Struktur geologi berupa patahan, dan lipatan. Eksplorasi di Pulau Seram telah menemukan 14 situs paleolitik. Dari analisis petrologi, alat-alat litik terbuat dari batuan jasper, chert, metagamping, batuapi, dan kuarsit. Batuan sebagai bahan baku alat litik, ditemukan di bagian tengah Pulau Seram, lalu disebarkan ke arah barat dan timur yang berelief datar.